Iranian EFL Learners’ Attitudes toward the Impact of Nonverbal Parameters upon their Learning Process - Omid Azad (Research in English Language Pedagogy, 2022)
Nonverbal cues include communicative markers like gestures, eye contact, nodding, tone of voice, and intonation among others which are associated and concomitant with language either consciously or unconsciously while playing significant roles in communication. The related literature demonstrates that nonverbal cues have great potential in foreign language learning. In this regard, it was predicted that EFL learners' attitudes toward nonverbal cues could affect their learning process significantly. This descriptive-analytical study was conducted to investigate students' attitudes toward their instructors' use of nonverbal cues in their communication and the extent to which using these elements could facilitate students' learning process. Utilizing a questionnaire as our instrument, we collected data from 50 undergraduate senior students of Linguistics at the University of Gonabad. Our rationale for choosing senior college students was to identify their attitudes toward their instructors' use of nonlinguistic cues since the beginning of their academic career at the university. Our findings revealed that our students had positive attitudes toward teachers' recruitment of nonlinguistic cues in their communication. Moreover, the parameter of gender was not found to affect students' attitudes with both males and females having positive attitudes toward the significance of nonverbal clues in communication. However, the parameter of learners' background experience of utilizing nonverbal clues in their native language was strongly related to their attitude toward EFL learning. Considering the predominant role of nonverbal communication in Iranian EFL settings, it was recommended that their recruitment in English teaching be taken more seriously.